2017
DOI: 10.1002/hep4.1021
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol exposure inhibits hepatocyte lipophagy by inactivating the small guanosine triphosphatase Rab7

Abstract: Alcohol consumption is a well‐established risk factor for the onset and progression of fatty liver disease. An estimated 90% of heavy drinkers are thought to develop significant liver steatosis. For these reasons, an increased understanding of the molecular basis for alcohol‐induced hepatic steatosis is important. It has become clear that autophagy, a catabolic process of intracellular degradation and recycling, plays a key role in hepatic lipid metabolism. We have shown that Rab7, a small guanosine triphospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 54 publications
(71 reference statements)
4
47
0
Order By: Relevance
“…(92,93) Chronic ethanol exposure may interfere with the nuclear localization of transcriptional lipophagic regulators, such as TFEB (as above), (94) or cause the harmful modulation of key mediators of LD interactions with the lipophagic machinery (as with Rab7). (74) Together, these data serve as strong evidence that lipophagy normally serves a hepatoprotective role in response to alcohol consumption. Disruption of this pathway over time, however, may provide an explanation for the prevalence of steatosis that persists with chronic alcohol abuse.…”
Section: Other Roles For Hepatic Lipophagymentioning
confidence: 86%
See 2 more Smart Citations
“…(92,93) Chronic ethanol exposure may interfere with the nuclear localization of transcriptional lipophagic regulators, such as TFEB (as above), (94) or cause the harmful modulation of key mediators of LD interactions with the lipophagic machinery (as with Rab7). (74) Together, these data serve as strong evidence that lipophagy normally serves a hepatoprotective role in response to alcohol consumption. Disruption of this pathway over time, however, may provide an explanation for the prevalence of steatosis that persists with chronic alcohol abuse.…”
Section: Other Roles For Hepatic Lipophagymentioning
confidence: 86%
“…This role of Rab7 is essential for starvation‐induced lipophagy as loss of Rab7 function after siRNA‐mediated knockdown or expression of a dominant‐negative mutant impaired LD breakdown . In a follow‐up study, it was observed that chronic ethanol exposure inhibits Rab7 activity, disrupts degradative compartment morphology and motility, and causes reduced LD turnover during the process of lipophagy . These findings provided some additional insights into how alcohol might exacerbate the progression of fatty liver.…”
Section: Role For the Rab Gtpases In Hepatic Lipophagymentioning
confidence: 94%
See 1 more Smart Citation
“…This result suggests that Rab7 may be an important LD-localized node for the regulation of hepatic lipophagy. Indeed, a very recent report shows that Rab7 is also a primary target for ethanol-induced hepatic steatosis [41]. The authors found that rats chronically fed an alcohol-containing diet are resistant to starvation-induced lipophagy, which ultimately results in liver steatosis.…”
Section: Proteins Involved In Lipophagy Inductionmentioning
confidence: 99%
“…In the first study, Schulze et al investigated the role of Rab7 in hepatocyte lipophagy under chronic ethanol exposure (7). Rab7 belongs to the Rab family of guanosine triphosphate (GTP) binding proteins that regulate intracellular vesicular trafficking.…”
mentioning
confidence: 99%